Integrating petrophysical characterization and reservoir evaluation of the Kafr ELSheikh formation in Sapphire field, Nile Delta, Egypt - Naiem Souilam Sobih; Ahmed Ahmed El Nagar; Ali Elsayed Abbas; Samir Shehab (Scientific Reports)
Abstract This study aims to integrate petrophysical characterization and reservoir evaluation for optimizing field development. The focus is on the Kafr Elsheikh formation, using iso-parametric maps to analyze key reservoir parameters such as effective porosity, shale content, net-pay thickness, permeability, hydrocarbon saturation, and water saturation across lateral sections. Petrophysical characterization is essential for understanding the reservoir quality and productivity potential. The study evaluates four wells—Sapphire 1, Sapphire-Da, Sapphire-Deep 1, and Sapphire-Dh—using well logs, including gamma ray, caliper, density, neutron, and resistivity, recorded in Las files. These wells are crucial for assessing the reservoir potential and development path of the Sapphire Field. Findings reveal that the Kafr Elsheikh formation has significant reservoir potential, with effective porosity ranging from 14 to 34%, water saturation between 15% and 45%, gas saturation from 55 to 85%, and net-pay thickness from 0.46 m to 23.8 m. Lithological analysis shows a composition of sandstone and shale within the formation. The developmental trajectory of Sapphire Field indicates increases in effective porosity and hydrocarbon saturation towards the central and northwest-southeast directions. Sapphire Da is identified as the most promising well, with 85% saturation, 29% effective porosity, and a net-pay thickness of 14.04 m. The study underscores the hydrocarbon reserves in the Kafr Elsheikh formation and advocates for further exploration and development wells to enhance productivity. Insights from iso-parametric maps are vital for future exploration and development within the Sapphire Field.